Electricity market governance and the historical performance of electricity transitions in European countries: insights from retrospective modeling - Marc Jaxa-Rozen; Xin Wen; Evelina Trutnevyte (Energy Strategy Reviews, 2025)
In the last decades, the governance of national electricity systems in Europe has experienced several shifts between market liberalization and policy intervention. However, there remains a lack of consistent evidence about impacts of electricity market governance on the performance of electricity systems. This work uses retrospective bottom-up modeling to explore potential links between electricity market governance in 31 European countries and their electricity system transitions during 1990–2019. We identify historical governance regimes based on indicators of market regulation, renewable electricity policy support, and combined regulation and policy support. To assess performance of electricity systems, we quantify deviations between modeled historical and least-cost pathways using net present costs per unit of supplied electricity, emissions intensity, transformation of generation mix, and share of new renewable technologies. Countries with earlier liberalization of electricity markets on average had higher unit net present costs, lower emissions intensity, and higher share of new renewable generation relative to modeled least-cost pathways. Countries combining late liberalization with high support for renewable generation, which includes countries with higher public ownership of incumbent low-carbon generation, had the lowest relative values for unit net present costs and emissions intensity. Further work could yield statistical insights on these patterns by combining our modeling approach with econometric analysis.